2008
DOI: 10.1111/j.1365-2109.2008.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish oil with vegetable oils in diets for jundiá (Rhamdia quelen Quoy and Gaimard 1824): effects on performance and whole body fatty acid composition

Abstract: The jundia Ł (Rhamdia quelen) is a siluriform with great potential for aquaculture in South America. Fish oil is a raw material in diets for ¢sh. However, the ¢sheries that provide ¢sh oil have reached their limit of sustainability. Thus, the use of alternative sources for this ingredient is primordial. The aim of this study was to evaluate the performance and body composition of the jundia Ł fed with di¡erent sources of the vegetable oils. Jundia Ł (1.0 AE 0.2 g) were fed for 31 days with ¢ve isonitrogenous (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
1
24
0
5
Order By: Relevance
“…Therefore, productive performance of Nile tilapia supplemented with (Bell et al, 2003;Mourent et al, 2005;Vargas et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, productive performance of Nile tilapia supplemented with (Bell et al, 2003;Mourent et al, 2005;Vargas et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Like other vertebrates, fish cannot produce linoleic (18:2 n-6) and linolenic acid (18:3 n-3) and therefore need to obtain these essential fatty acids from their diet, according to species-specific requirements (New 1987;Valenzuela et al 2014). Fish can convert 18-carbon PUFA into highly unsaturated fatty acids (HUFA) of the same omega 3 series, namely eicosapentanoic acid (EPA; 20:5 n-3) and docosaexanoic acid (DHA; 22:6 n-3) (Vargas et al 2008;Tanamati et al 2009;Kamarudin et al 2012). In human nutrition, HUFAs are associated with the prevention Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Flaxseed oil is a potential candidate for use in tropical fish feed. In fact, the carcass quality of jundias (Rhamdia quelen) improved with dietary flaxseed inclusion (Vargas et al 2008). In addition, vegetable ingredients can be more suitable than those of animal origin.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that lambari have the capacity of elongation and desaturation due to a greater presence of DHA and a decrease in linolenic acid levels found in the muscle tissue than in diets with soybean oil and tilapia residue oil, for both sexes. This fact was also evident in other Brazilian species of freshwater fish, such as pintado, Pseudoplatystoma coruscans (Martino et al, 2002;Tanamati et al, 2009); jundiá, Rhamdia quelen (Vargas et al, 2008); pacu, Piaractus mesopotamicus (Tanamati et al, 2009); and matrinxã, Brycon cephalus (Almeida & Franco, 2007).…”
Section: Resultsmentioning
confidence: 62%
“…Studies conducted by Izquierdo et al (2003), Martínez-Llorens et al (2007), Martino et al (2002) and Vargas et al (2008) verified that the fatty acid profile of the diet reflects on the composition of fatty acids in fish tissue. Linoleic acid (C18: 2n-6) was found at higher levels among the polyunsaturated fatty acids in the oils and the experimental diets, except for salmon oil, which showed to have a higher concentration of DHA.…”
Section: Resultsmentioning
confidence: 90%